2016
DOI: 10.1016/j.jvs.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified Frailty Index to predict mortality in vascular surgery patients

Abstract: The mFI was a better discriminator of mortality than other risk indices; however this was only significant for the open cohort. The mFI was also a better discriminator of class IV complications for the open and endovascular AAA repair groups. These data suggest that mFI should be used in place of previously recognized risk indices to define perioperative mortality after open vascular surgery and risk of major complications after aneurysm repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 29 publications
3
85
0
2
Order By: Relevance
“…Ehlert et al 11 compared the mFI to Lee Cardiac Risk Index and the American Society of Anesthesiologists Physical Status Classification to predict 30-day mortality in patients undergoing open carotid revascularization, abdominal aortic aneurysm repair, or lower extremity revascularization using the NSQIP database and found that the frailty score was the best discriminator of mortality. Kraiss et al have developed and validated a frailty model in the Vascular Quality Initiative data using 7 data elements and procedure-based risk estimates to predict 9-month mortality after arterial reconstruction with an AUC of 0.76.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ehlert et al 11 compared the mFI to Lee Cardiac Risk Index and the American Society of Anesthesiologists Physical Status Classification to predict 30-day mortality in patients undergoing open carotid revascularization, abdominal aortic aneurysm repair, or lower extremity revascularization using the NSQIP database and found that the frailty score was the best discriminator of mortality. Kraiss et al have developed and validated a frailty model in the Vascular Quality Initiative data using 7 data elements and procedure-based risk estimates to predict 9-month mortality after arterial reconstruction with an AUC of 0.76.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 This biologic syndrome, which results in decreased resistance to stressors and increased vulnerability to morbidity, has been termed frailty. 12 Multiple frailty indices have been developed to scale a patient's AD and predict their operative risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study assessing the efect of frailty on outcomes after vascular surgery showed that frailty, assessed by the modiied Frailty Index (mFI), predicted mortality in patients undergoing open procedures and Clavien-Dindo class IV (life-threatening) complications for both open and endovascular abdominal aortic aneurysm repairs [85]. Afecting disposition and, hence, patient wellness and health-care expenditure, frailty also increases the propensity of home-dwelling patients classiied as frail to be discharged to a facility other than their home after elective vascular interventions [86].…”
Section: Frailty and Peripheral Arterial Disease (Pad)mentioning
confidence: 99%
“…10,11 This biologic syndrome, which results in decreased resistance to stressors and increased vulnerability to morbidity, has been termed frailty. 12 …”
Section: Introductionmentioning
confidence: 99%